The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1002/jcb.21005
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of regucalcin enhances glucose utilization and lipid production in cloned rat hepatoma H4‐II‐E cells: Involvement of insulin resistance

Abstract: The role of regucalcin, which is a regulatory protein in intracellular signaling pathway, in the regulation of glucose utilization and lipid production was investigated using the cloned rat hepatoma H4-II-E cells overexpressing regucalcin. The hepatoma cells (wild-type) and stable regucalcin/pCXN2-transfected cells (transfectant) were cultured for 72 h in a medium containing 10% fetal bovine serum (FBS) to obtain subconfluent monolayers. Cells with subconfluency were cultured for 24 or 72 h in medium containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…From the proteome of H4-II-E cells exposed to insulin and TNF-α, it has been proposed that regucalcin has a role associated with proteins which are involved in insulin resistance (31). This was confirmed by our previous observations that overexpression of regucalcin plays a role in inducing insulin resistance in H4-II-E cells (24).…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…From the proteome of H4-II-E cells exposed to insulin and TNF-α, it has been proposed that regucalcin has a role associated with proteins which are involved in insulin resistance (31). This was confirmed by our previous observations that overexpression of regucalcin plays a role in inducing insulin resistance in H4-II-E cells (24).…”
Section: Discussionsupporting
confidence: 68%
“…Overexpression of regucalcin has been shown to enhance glucose utilization and lipid production in cloned rat hepatoma H4-II-E cells, and to induce insulin resistance in the cells (24). Previous studies have shown that insulin resistance may be modeled in H4-II-E liver cells in tissue culture with the use of the cytokine tumor necrosis factor-α (TNF-α) and insulin (30).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…How does a change in RGN level relate to the pathogenesis of HCC? RGN is a Ca binding protein and is important for intracellular Ca homeostasis and in signaling pathways controlling glucose utilization and lipid production [18][19][20]. RGN is sensitive to oxidative modification and a more than two-fold increase in the carbonyl content has been reported in old mice [21].…”
Section: Discussionmentioning
confidence: 99%